Gustavo Alberto: “invention” and circulation of the first patented school desk in Brazil (1881-1884) (Educação e Pesquisa, 2022)
One of the most central material elements in schools at the end of the 19th century was, undoubtedly, the furniture used by the students: the school desk. Appearing as an alternative to the old collective benches and tables, disseminated at the World’s Fairs, debated at Pedagogical and Hygiene Congresses, the creation and production of the so-called chair-desks contributed to establish a rising school industry. In the Empire of Brazil, this matter came to be vigorously debated in the 1880s. With few exceptions, the investigation of the beginnings of this production of school desks in the country is still a subject lacking historiographical treatment. In this context, this paper aims at investigating the process of “invention” and circulation of the first patented school desk in Brazil, on the initiative of its inventor, Professor Gustavo José Alberto, between 1881 and 1884. Therefore, it is based on the methodological resources of microhistory and uses, as privileged sources, periodicals of that time published in the Imperial Court and official reports. The findings point out that the interest by the professor in producing a prototype of a school desk seems that it resulted from his teaching experience and contact with pedagogical debates – then in progress – in which he played an active role. At the same time, upon creating a desk model to be used in his school, he decided to patent it in the Ministry of Agriculture in order to subsequently offer it to the government. At that moment, the government was making significant purchases of this material, both via imports and local manufacturing.